Tracing Theology and Historical Praxis in Early Muslim-Christian Relations - Adeoye, Moses Adeleke; Arifudin, Muhammad (Indonesian Journal of Religious, 2025)
In an era marked by religious pluralism and socio-political tensions, constructive engagement between Muslims and Christians has become both a theological necessity and a social imperative. This paper explored the theological and historical praxis of charity in early Muslim and Christian communities as a basis for fostering deeper mutual understanding and cooperation. Employing a qualitative, historical-comparative method, the research draws on primary sources—including the Qur’an, Hadith, the New Testament, and early theological writings—supplemented by secondary scholarly interpretations. Through historical-critical analysis, theological exegesis, and comparative theology, the study examines how zakat and ṣadaqah in Islam, and agape-inspired almsgiving in Christianity, were developed and practised as religious imperatives and social ethics. Findings reveal that Islam conceptualises charity primarily as an obligatory act of worship and social justice, rooted in divine command, while Christianity emphasises voluntary, grace-filled giving as a manifestation of God’s unconditional love. Despite these differences, both traditions converge on the ethical imperatives of compassion, equity, and care for the marginalised. Furthermore, the study identifies practical pathways for interfaith cooperation, including joint educational initiatives, scholarly collaborations, leadership engagement, and grassroots charitable projects. The research concludes that charity offers a transformative platform for Muslim-Christian dialogue, serving as both a theological bridge and a social resource. It contributes to comparative theology and interfaith studies by demonstrating that shared commitments to charity can advance peacebuilding, ethical solidarity, and constructive coexistence in pluralistic societies.